Testing the Electrical Safety Aspects of The Emergency Shut Down Multi Indicator (Esin) Innovation Tool for Refueling De-Refueling Trucks (RDT) at The Mutiara Palu Aircraft Filling Depot - Ratih Mar'atus Sholihah; Irwan Mahmudi; Lutfiyana Andi Anshar (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
As the commercial and trading subholding of PT Pertamina (Persero), Pertamina Patra Niaga also provides aviation fuel to airlines. The aviation fuel refueling place is called the Aircraft Refueling Depot. One of the aircraft filling depots in Palu is the Mutiara Aircraft Filling Depot, located in the Mutiara Sis Al-Jufri Airport Area. The Mutiara Aircraft Refueling Depot uses a Refueling De-Refueling Truck (RDT) to fill aircraft with fuel while on the ground. This refueler unit can also pump and store fuel from aircraft. One of the problems when refueling aviation fuel by RDT at the Mutiara Aircraft Filling Depot was the activation of the emergency stop when the Certified Refueler Operator (CRO) was carrying out the service. The aviation fuel-filling system stopped without anyone realizing it, causing flight delays. The active emergency stop without a clear indicator initiates the FT Prove Pin Point group to create an Emergency Shut-Down Multi-Indicator (ESIn) tool that can monitor the active status of the emergency fuel or engine stop. Before the ESIn tool is used, one of the steps that must be carried out is a feasibility test on electrical safety aspects. Testing is carried out using three criteria, namely visual testing, component electrical parameters, and performance. Based on visual and performance testing, the tool is in good condition and can operate according to the planned purpose. Likewise, when testing component electrical parameters, the measured parameter values show values according to applicable electrical standards.